Complete mitochondrial genome sequence of nanday conure, Aratinga nenday (Psittaciformes: Psittacidae) - Liu, Da-Wei (Mitochondrial DNA B Resour, 2019)
Here, we report the complete mitochondrial genome of Aratinga nenday. It was found to be a closed circular molecule of 16,983 bp, containing 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes, and 1 non-coding control region. The overall base composition was 54.03% A + T and 45.973% G + C contents. The complete mtDNA of A. nenday and other 14 species were subjected to phylogenetic analysis by the neighbour-joining method and the Kimura 2-parameter model, which showed A. nenday to be a sister to the congeneric Aratinga solstitialis.